2018
DOI: 10.1007/s00784-018-2650-4
|View full text |Cite
|
Sign up to set email alerts
|

Distances of root apices to adjacent anatomical structures in the anterior maxilla: an analysis using cone beam computed tomography

Abstract: Objectives The aim was to assess the anatomical relationship of anterior maxillary teeth to the nasal floor in patients referred for apical surgery. Materials and methods Cone beam computed tomographic images (CBCT) of 83 patients were analysed retrospectively to quantify the distances between the root apices of maxillary anterior teeth (canine to canine) to the nasal floor or maxillary sinus (whichever was closer). Secondary outcome variables were the distances of the periapical lesion to the nasal floor, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
1
6
0
9
Order By: Relevance
“…The mean BH of the anterior maxillary bone was 12.24±2.62 in the present study.The highest BH was related to the canines, lateral teeth, and central teeth, respectively.This result can be explained by the root distance of anterior teeth from anatomical structures, such as the floor of the nasal cavity and maxillary sinus. The average distance between the roots of anterior teeth and these structures was 8.54 mm in central teeth, 9.49 mm in lateral teeth, and 5.39 mm in canines; [22] this result is in line with the findings reported by Dina Ahmed et al [20].…”
Section: Discussionsupporting
confidence: 91%
“…The mean BH of the anterior maxillary bone was 12.24±2.62 in the present study.The highest BH was related to the canines, lateral teeth, and central teeth, respectively.This result can be explained by the root distance of anterior teeth from anatomical structures, such as the floor of the nasal cavity and maxillary sinus. The average distance between the roots of anterior teeth and these structures was 8.54 mm in central teeth, 9.49 mm in lateral teeth, and 5.39 mm in canines; [22] this result is in line with the findings reported by Dina Ahmed et al [20].…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between the maxillary sinus oor and posterior teeth has already been evaluated in various studies [4,[10][11][12][13][14][15][16]. In contrast, few studies have addressed the relationship between the maxillary sinus oor and canine apex [4,[20][21][22]. AL-Qasab et al [22] evaluated this relationship in a limited sample size (30 individuals) and in periapical radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…AL-Qasab et al [22] evaluated this relationship in a limited sample size (30 individuals) and in periapical radiographs. Ducommun et al [21] evaluated 83 CBCT images for the distance between the apices of the anterior teeth to the nasal oor or maxillary sinus, whichever was closer, and they did not report the results separately for each structure. Their study also included the anterior teeth with apical lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 This study found that, the rehabilitation effect of the observation group is better than that of the control group, the recovery time is shorter than the control group, the grade of ligament injury at 1, 2, and 3 months of rehabilitation treatment was better than that of the control group, it shows that carrying out sports medicine ultrasound examinations at different stages of rehabilitation can shorten the recovery time of patients, improve its rehabilitation effect, promote the recovery of its ligament damage. 10 The reason for the analysis may be ultrasound evaluation during rehabilitation treatment, can make timely judgments of ligament thickness, effusion volume and echo, etc., it can not only evaluate the effect of rehabilitation, but also guide the development of rehabilitation treatment.…”
Section: Discussionmentioning
confidence: 99%